Teaching the Holocaust and National Socialism in Austria: politics of memory, history classes, and empirical insights. Issue 3 (3rd July 2017) - Kühberger, Christoph
ABSTRACT: This article deals with the politics of memory in Austria with regard to National Socialism and the Holocaust since 1945 by juxtaposing the way the matter is raised in Austrian society in general with how the teaching of history has evolved. The ways in which National Socialism and the Holocaust are addressed in the instruction of Austrian secondary school students are investigated by exploring a recent survey in Salzburg and the latest findings from research into Austrian history textbooks. These findings are considered in context and in comparison with recent findings from England. The article concludes with reflections on future changes in Austrian Holocaust education.